Strategies and Challenges for Managing Human Influenza in the Iranian hospitals: A Qualitative Study in Yazd province, Central part of Iran - Sajjad Bahariniya; Milad Shafii; Farzan Madadizadeh; Mohammad Sharif Yazdi (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract: Introduction: Influenza virus is one of the deadliest viruses that has threatened the human population over the years. Every year, organizations and hospitals must be prepared to deal with the disease and treat people with the flu and be able to manage the disease in the hospital. The aim of this study was to identify hospital management strategies for human influenza in Yazd province, central part of Iran. Methods: This study was a qualitative study with inductive conventional approach. A total of 14 main hospitals in Yazd province were surveyed in 2021. The study population included heads and managers of hospitals, nurses, educational and clinical supervisors, metrons, officials of the quality improvement office and the infection Control Committee. Participants were selected using snowball sampling method. semi structured interviews were used to collect data. The sample size in this study was up to information saturation. Content analysis method was used to analyze the data. Results: Using the opinions and views of 38 managers and officials of selected hospitals in Yazd province, data saturation was obtained. The most important tasks of the hospital management in terms of influenza control and management were divided into 5 areas (field measures, support, training, awareness, protection   and measures in the field of human resources). The major challenges   regarding the influenza control and management were classified into 3 areas: hospital (health), macro (university, provincial, national and Ministry of Health guidelines) and community level. Finally, the most important solutions and suggestions were categorized in these 3 key areas. Conclusion: Based on the categorized challenges and problems, as well as the classification of the most important strategies and suggestions, useful action can be taken to    the control and management of influenza, both at the hospital level and in the community, in Iranian hospitals especially in Yazd province.